Respiratory involvement in connective tissue diseases - Xanthouli, Panagiota; Echampati, Ishan; Lorenz, Hanns-Martin; Heußel, Claus Peter; Benjamin, Nicola (European journal of internal medicine, 2024)
Pulmonary involvement is doubtless one the most fatal organ manifestations of the autoimmune rheumatic diseases (ARD) and involves the parenchyma, the vessels, the respiratory system itself, but also the muscles and the pleura. Close and regular screening assessments, identification of risk factors, clinical signs associated with the existence of lung disease should alarm the involved physicians treating these patients. The accurate classification is essential, as different treatment options are nowadays available. Pulmonary manifestations of ARD will be analyzed in this review article with special emphasis on interstitial lung disease and pulmonary hypertension.
Online verfügbar: 14 October 2023
Gesehen am 11.07.2024